Proposal for the applicability of modified Breslow (measured from the basal membrane) as a predictor of survival and sentinel lymph node outcome in patients with cutaneous melanoma - Asato, Marcel Arakaki [UNESP]; Moares Neto, Francisco Alves; Moraes, Marcelo Padovani de Toledo [UNESP]; Ocanha-Xavier, Juliana Polizel [UNESP]; Takita, Luiz Carlos; Marques, Mariangela Esther Alencar [UNESP]; Xavier-Júnior, José Cândido Caldeira [UNESP] (Elsevier, 2024)
Background: Cutaneous melanoma is a neoplasm with a high mortality rate and risk of metastases to distant organs. The Breslow micrometric measurement is considered the most important factor for evaluating prognosis and management, measured from the granular layer to the deepest portion of the neoplasm. Despite its widespread use, the Breslow thickness measurement has some inaccuracies, such as not considering variations in the thickness of the epidermis in different body locations or when there is ulceration. Objective: To evaluate the applicability of a modified Breslow measurement, measured from the basal membrane instead of from the granular layer, in an attempt to predict sentinel lymph node examination outcome and survival of patients with melanoma. Methods: A retrospective and cross-sectional analysis was carried out based on the evaluation of slides stained with hematoxylin & eosin from 275 cases of melanoma that underwent sentinel lymph node biopsy from 2008 to 2021 at a reference center in Brazil. Results: Analysis of the Cox model to evaluate the impact of the Breslow measurement and the modified Breslow measurement on survival showed that both methods are statistically significant. Logistic regression revealed a significant association between both measurements and the presence of metastasis in sentinel lymph nodes. Conclusion: Measuring melanoma depth from the basal membrane (modified Breslow measurement) is capable of predicting survival time and sentinel lymph node outcome, as well as the conventional Breslow measurement.
Keywords: Melanoma; Neoplasm staging; Pathology; Skin neoplasms